2018
DOI: 10.1007/s10616-018-0220-x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid inhibits senescence in mesenchymal stem cells through ROS and AKT/mTOR signaling

Abstract: Mesenchymal stem cell (MSC) aging seriously affects its function in stem cell transplantation for treatment. Extensive studies have focused on how to inhibit senescence in MSCs. However, the mechanism of senescence in MSC was not clear. In this study, we used D-galactose to induce MSC aging. Then we found that the number of aging cells was increased compared with untreated MSCs. We discovered that ascorbic acid could inhibit the production of reactive oxygen species (ROS) and activation of AKT/mTOR signaling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Along with the effects of vitamin C on vascularization, metabolism, and inflammation mentioned above, it has also antioxidant effects. In this regard, vitamin C can postpone aging in MSCs via prevention of the ROS production and AKT/mTOR signaling [21]. Arab et al [20] found that antioxidant effect of ascorbic acid could ameliorate increased oxidative stress induced by malathion in the rats ovary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the effects of vitamin C on vascularization, metabolism, and inflammation mentioned above, it has also antioxidant effects. In this regard, vitamin C can postpone aging in MSCs via prevention of the ROS production and AKT/mTOR signaling [21]. Arab et al [20] found that antioxidant effect of ascorbic acid could ameliorate increased oxidative stress induced by malathion in the rats ovary.…”
Section: Discussionmentioning
confidence: 99%
“…Application of free radicals scavengers can protect ovary from the damage of oxidative stress [181920]. Vitamin C (L-ascorbic acid) is a natural antioxidant scavenging ROS effectively [2122]. In addition, useful effects of vitamin C on metabolism, collagen synthesis, vasculogenesis, aging, cell proliferation, and differentiation has been reported previously [21222324].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional potential regulators: The AKT pathway plays an important role in the rejuvenation of features and functions of aged MSCs. This pathway can act via ERBB4/PI3K/AKT[ 112 ], lactoferrin/AKT[ 113 ], Vc/AKT/mTOR[ 114 ], and fucoidan/FAK-Akt-TWIST axes[ 115 ]. Administration of rapamycin, an inhibitor of the mTOR signaling pathway, raised the expression level of NANOG, postponed replicative arrest, and enhanced the lifespan increment of BM-MSCs[ 116 ].…”
Section: Cellular Rejuvenation Strategiesmentioning
confidence: 99%
“…Activation of autophagy through Sirtuin mobilization [143,156,158] Ascorbic acid Reduction in ROS levels and inhibition of the AKT/mTOR signalling [159] C1q and tumour necrosis factor-related protein 9 (CTRP9)…”
Section: #176}mentioning
confidence: 99%